Promotion of BST2 expression by the transcription factor IRF6 affects the progression of endometriosis - Li, Jixin; He, Yanan; Qu, Yanjun; Ren, Chengcheng; Wang, Xiaotong; Cheng, Yan; Sun, Liyuan; Zhang, Xin; Zhang, Guangmei (Frontiers in Immunology, 2023)
Background: Endometriosis (EM) is a benign, multifactorial, immune-mediated inflammatory disease that is characterized by persistent activation of the NF‐κB signaling pathway and some features of malignancies, such as proliferation and lymphangiogenesis. To date, the pathogenesis of EM is still unclear. In this study, we investigated whether BST2 plays a role in the development of EM. Methods: Bioinformatic analysis was performed with data from public databases to identify potential candidate targets for drug treatment. Experiments were conducted at the cell, tissue, and mouse EM model levels to characterize the aberrant expression patterns, molecular mechanisms, biological behaviors of endometriosis as well as treatment outcomes. Results: BST2 was significantly upregulated in ectopic endometrial tissues and cells compared with control samples. Functional studies indicated that BST2 promoted proliferation, migration, and lymphangiogenesis and inhibited apoptosis in vitro and in vivo. The transcription factor (TF) IRF6 induced high BST2 expression by directly binding the BST2 promoter. The underlying mechanism by which BST2 functions in EM was closely related to the canonical NF‐κB signaling pathway. New lymphatic vessels may serve as a channel for the infiltration of immune cells into the endometriotic microenvironment; these immune cells further produce the proinflammatory cytokine IL-1β, which in turn further activates the NF‐κB pathway to promote lymphangiogenesis in endometriosis. Conclusion: Taken together, our findings provide novel insight into the mechanism by which BST2 participates in a feedback loop with the NF‐κB signaling pathway and reveal a novel biomarker and potential therapeutic target for endometriosis.